Evaluation of n-type ternary metal oxide NiMn2O4 nanomaterial for humidity sensing - Gawli, Yogesh; Badadhe, Satish S.; Basu, Aniruddha; Guin, Debanjan; Shelke, Manjusha V.; Ogale, Satishchandra (Sensors and Actuators B-Chemical, 2014)
Synthesis of mono-dispersed oleic acid (OA) capped NiMn2O4 (NMO) nanoparticles and their use for humidity sensing is reported. Oleic acid capped NMO (NMO-cOA) nanoparticles are synthesized from nickel oleate and manganese oleate complex. NiMn2O4 is obtained by removing oleic acid capping at 500 degrees C in air. X-ray diffraction analysis shows formation of pure NiMn2O4 phase which is also confirmed by HRTEM-SAED analysis. The TEM analysis also shows that the nanoparticles are nearly mono-dispersed. Doctor bladed films of NMO nanoparticles are seen to exhibit excellent humidity sensing property. The resistivity is seen to change by two orders with humidity change from 11% RH to 92% RH with fairly good linearity over the entire range. The response and recovery times are also fast. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Humidity; Impedance; Nanoparticles; NiMn2O4; Oleic acid; Sensor

Starch (Tapioca) to carbon dots: an efficient green approach to an on-off-on photoluminescence probe for fluoride ion sensing - Basu, Aniruddha; Suryawanshi, Anil; Kumawat, Begraj; Dandia, Anshu; Guin, Debanjan; Ogale, Satishchandra B. (Analyst, 2015)
Photoluminescent carbon dots of 4-5 nm size were prepared from starch (Tapioca Sago) through a solution method under mild conditions. The as-prepared carbon dots were used as photoluminescence probes for highly anion selective fluoride ion detection in aqueous solutions. A ready-to-use device is also demonstrated.

CO2 Laser direct written MOF-based metal-decorated and heteroatom-doped porous graphene for flexible all-solid-state microsupercapacitor with extremely high cycling stability - Basu, Aniruddha; Roy, Kingshuk; Sharma, Neha; Nandi, Shyamapada; Vaidhyanathan, Ramanathan; Rane, Sunit; Rode, Chandrashekhar V.; Ogale, Satishchandra B. (ACS Applied Materials & Interfaces, 2016)
Over the past decade, flexible and wearable microelectronic devices and systems have gained significant importance. Because portable power source is an essential need of such wearable devices, currently there is considerable research emphasis on the development of planar interdigitated micro energy-torage devices by employing diverse precursor materials to obtain functional materials (functional carbon, oxides, etc.) with the desirable set of properties. Herein we report for the first time the use of metal organic framework (MOF) and zeolitic imidazolate framework (ZIF-67) for high-wavelength photothermal laser direct writing of metal-decorated, heteroatom-doped, porous few-layer graphene electrodes for microsupercapacitor application. We argue that the specific attributes of MOF as a precursor and the high-wavelength laser writing approach (which creates extremely high localized and transient temperature (>2500 degrees C) due to strong absorption by lattice vibrations) are together responsible for the peculiar interesting properties of the carbon material thus synthesized, thereby rendering extremely high cycling stability to the corresponding microsupercapacitor device. Our device exhibits near 100% retention after 200 000 cycles as well as stability under 150 degrees bending.

Highly stable laser-scribed flexible planar microsupercapacitor using mushroom derived carbon electrodes - Yadav, Poonam; Basu, Aniruddha; Suryawanshi, Anil; Game, Onkar S.; Ogale, Satishchandra (Advanced Materials Interfaces, 2016)
A report is presented on the fabrication of all solid-state interdigitated flexible microsupercapacitor using ultrafast and highly scalable laser scribing technique, using highly mesoporous carbon synthesized from biomass (mushroom) with hydrothermal preprocessing. The specific protocol used for carbon synthesis renders some unique property features to the material (surface area of 2604 m(2) g(-1) with hierarchical pore size distribution) in the context of supercapacitor electrode application. A polyvinyl alcohol (PVA)-H2SO4 gel electrolyte is used for electrochemical measurements. The microsupercapacitor shows high cyclic stability up to 15000 cycles. Moreover it shows nearly 90% stability after 1000 bending cycles at 60 degrees angle. It also retains its performance even under 120 degrees bending condition. This work represents a facile and fast technique for microscaled device fabrication that can be easily commercialized. Moreover, the mushroom-derived carbon used to make the electrodes holds great promise in context of the stability and flexibility of flexible supercapacitors.

Robust highly flexible all-solid-state micro pseudocapacitor based on ternary oxide CuCo2O4 having ultrathin porous nanowall type morphology blended with CNT - Basu, Aniruddha; Bhardwaj, Monika; Gawli, Yogesh; Rode, Chandrasekhar V.; Ogale, Satishchandra B. (Chemistryselect, 2016)
In this work we demonstrate a facile approach to the fabrication of all solid state flexible interdigitated micro pseudocapacitor device using pre-synthesized CuCo2O4 (CCO) ternary metal oxide as the electrode material. The hydrothermally synthesized CCO exhibits a peculiar 3D interconnected aligned porous nanowall type morphology which is highly desirable for storage as well as charge transfer. The device is fabricated using CO2 laser scribing technique and the PVA-H3PO4 gel electrolyte is used as the electrolyte. The as-synthesized CCO as well as its blend with 10 wt.% CNT are examined for the electrochemical performance. CNT blending is shown to reduce the charge transfer resistance dramatically, thereby enhancing the pseudo capacitance. The areal capacitance of 2.29 mF cm(-2) is obtained from the solid state device. Moreover, the CCO-CNT electrode also shows a high stability upto 9000 cycles without a sign of further decay. Importantly, the devices also retain over 65% of their initial capacitance after 1000 large angle (608) bending cycles and 93% of the initial capacitance under 1208 bending condition, thanks to the mechanical flexibility afforded by CNTs without disrupting conducting paths.

Laser patterning of boron carbon nitride electrodes for flexible micro-supercapacitor with remarkable electrochemical stability/capacity - Karbhal, Indrapal; Basu, Aniruddha; Patrike, Apurva; Shelke, Manjusha V. (Carbon, 2021)
High performance, all solid-state planar micro-supercapacitor (MSC) with interdigitated Boron carbon Nitride (BCN) electrodes are fabricated via fast, scalable laser patterning technique. Heteroatom doping desirably enhances the electrochemical activity of carbon electrodes. This BCN based micro-supercapacitor showed comparatively very high specific capacitance of 72 mFcm(-2) at a current density of 0.15 mAcm(-2). Even at a high current density of 1 mAcm(-2) device showed specific capacitance as high as 17 mFcm(-2). It has demonstrated excellent electrochemical stability when tested up to 80000 cycles without any sign of further decay in capacity/efficiency. This device showed stable capacity even after bending at 150 degrees angle, for 1500 times during cycling showing remarkable flexibility. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: BCN; Co-doping; Energy storage; Flexible; Laser patterning; Micro-supercapacitor